Effectiveness of Metanil Yellow Adsorption Using CTAB-Modified Activated Carbon from Areca Nut Husk (Areca catechu L.) - Sri Rahayu; Ratna Sari Dewi (Universitas Negeri Medan, 2025)
This study investigates the adsorption efficiency of Metanil Yellow using activated carbon derived from areca nut husk (Areca catechu L.), which was chemically activated with KOH and modified with CTAB surfactant. The adsorbent was characterized using FTIR and UV-Vis spectroscopy to identify functional groups and determine optimum adsorption parameters. FTIR analysis confirmed the presence of functional groups such as –CH₂, –C–N, and –N⁺(CH₃)₃, indicating successful surface modification. UV-Vis analysis showed that the maximum adsorption occurred at a wavelength of 494 nm. The optimum conditions were achieved at an adsorbent mass of 1.5 g, dye concentration of 15 ppm, and contact time of 60 minutes, with adsorption efficiency reaching over 97%. These findings suggest that CTAB-modified areca nut husk activated carbon has strong potential as an effective and low-cost adsorbent for removing dyes from wastewater.